CONTRIBUTION OF ASSERTIVE BEHAVIOR TOWARD EMPLOYEE’S SELF-ESTEEM - Ratna Maharani Hapsari; Retnaningsih Retnaningsih (Universitas Gunadarma, 2007)
Employee is one the most important element in a company. Each company has its own target and it’s easier to reach the target when company has good employees. Employee with good quality can be known for those who has high self-esteem, and to get higher self-esteem, employee must have assertive behavior as an important characteristic. The aim of this study is know the contribution of assertive behavior to self-esteem in employee. Participants of this study is 105 employee and this study uses quantitative approach. Simple regression shows F score around 53.159 (p < 0.01). The result tells us about the contribution of assertive behavior to self-esteem in employee. R2 score shows that the contribution of assertive behavior to self-esteem is about 34%, which means the rest contribution is considered from the other factors.Keywords: assertive behavior, self-esteem, employee